Revealing the Most Vulnerable Groups: Courtesy Stigma in Caregivers of Autistic Persons in Quebec - Valderrama, Alena; Nikièma, Béatrice; Forgeot d’Arc, Baudouin; Guerrero, Lucila; Giroux, Mathieu (Frontiers in Psychology, 2024)
Abstract Caregivers of autistic persons often face with "courtesy stigma," a phenomenon that adversely affects their well-being. Understanding the repercussions of this stigma is crucial not only for caregivers' mental health but also for the quality of care provided to their dependent. This study aimed to explore courtesy stigma among caregivers of autistic persons in Quebec, examining its prevalence and im-pact in order to identify groups that are particularly susceptible to negative out-comes. Methods This study used a cross-sectional online survey methodology employing quota sampling to collect responses from 194 participants. Data were collected using a computer-assisted web interview (CAWI) platform. The impact of courtesy stigma was specifically measured in terms of care burden, mental health, and overall well-being of caregivers. Results The findings revealed that caregivers frequently experience rejection, isolation, and work-related challenges. Notably, caregivers' health was below average com-pared with the subpopulations with the lowest health levels in Quebec. The care-givers who are the most vulnerable to negative outcomes included female care-givers, those aged 45 or older, financially strained households, caregivers of chil-dren requiring elevated levels of support, caregivers who isolated due to their au-tistic dependents, and those who experienced stigmatization directed at them-selves or their children in the form of rejection. Interestingly, 60% of respondents reported that the caregiving burden was "not at all" to "somewhat" difficult, raising questions about factors that may mitigate caregiving challenges over time. Conclusion Negative outcomes vary depending on certain risk factors and individual character-istics. This study underscores the need for targeted public policies and interven-tions, particularly for those at a higher risk of experiencing the negative effects of courtesy stigma on the burden of care, overall health, and mental health. By tailor-ing resources and support for these priority groups, we can better address the challenges faced by families of autistic persons.